2011
DOI: 10.4314/thrb.v13i3.67430
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and awareness of oral manifestations among people living with HIV/AIDS attending counselling and treatment centres in Iringa Municipality, Tanzania

Abstract: There is limited literature on the magnitude of oral manifestations and the extent of awareness on its occurrence in people living with HIV/AIDS (PLWHA) in Tanzania. The objective of this study was to assess the magnitude of, and extent of awareness on oral manifestations among PLWHA attending counselling and treatment centres (CTC) in Iringa Municipality in south-western Tanzania. A convenient sample of 200 PLWHA was included in the study in two CTC. Each participant was interviewed using a structured questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…30 , but higher than the 23.5% reported in Iringa by Mwangosi et al. 31 Some of the many possible explanations for these differences refer to the levels of ART available, the specific management regimen offered to each individual with oral lesions, which is personalised to each patient, and to differences in practices at various CTCs 26 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…30 , but higher than the 23.5% reported in Iringa by Mwangosi et al. 31 Some of the many possible explanations for these differences refer to the levels of ART available, the specific management regimen offered to each individual with oral lesions, which is personalised to each patient, and to differences in practices at various CTCs 26 .…”
Section: Discussionmentioning
confidence: 89%
“…Participants were also asked to recall and name any oral manifestation they had experienced at any time in the past. This interview was followed by a short clinical assessment of the participant’s oral health status in which all soft and hard tissue lesions were noted, along with details of the site involved, according to the criteria defined elsewhere by Mwangosi and Majenge 31 . Participants who were not willing to join the study were excluded; the number of these was negligible ( n = 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports from few countries in the Sub Saharan Africa present a closely similar picture. In Tanzania Hamza et al, (2006) observed oral lesions in 39.5% of the patients whereas Fabian et al, (2009) reported at least one oral lesion in 45% of the PLWHA they examined while Mwangosi & Majenge, (2011) reported a prevalence of oral manifestations to be 23.5%. In Kenya Butt et al, (2001) reported over 80% prevalence of candidiasis of the hyperplastic, erythematous and pseudomembraneous types, 27.9% prevalence of lymphadenopathy and angular cheilitis, while oral Kaposi's sarcoma was seen in 13% of the patients.…”
Section: Trend Of Occurrence Of Oral Manifestations Before Arv and Dumentioning
confidence: 97%
“…Though the incidence and prevalence of opportunistic infection have been reduced worldwide due to use of anti-retroviral therapy (ART) (Diz Dios et al, 2001;Ceballos-Salobrena et al, 2004), oral candidiasis remains the most frequent HIV-associated oral lesion in most developing countries including Tanzania. In Tanzania, oral candidiasis is the common condition in HIV infected patients with prevalence ranging from 20 % to 80 % (Schiødt et al, 1990;Hamza et al, 2006;Kahabuka et al, 2007;Mwangosi & Majenge, 2011).…”
Section: Introductionmentioning
confidence: 99%